ANALYSIS OF AC/DC/AC CONVERSION PROCESS IN DFIG AND BLDC MACHINE BY USING SEPIC CONVERTER IN THE FRONT END - Jeyapriya, M. (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
One of the most common solutions to the problem of feeding a three-phase induction motor from a single-phase line is using AC/DC/AC converter. An AC/DC/AC converter is composed by two stages, rectifying and inverting. The rectifying stage, or front-end, is generally implemented using a diode bridge rectifier or a boost rectifier. This paper evaluates the performance of a Single Ended Primary Inductor Converter(SEPIC) derivedÂ  Power Factor Correction(PFC) rectifier used as a front-end of an AC/DC/AC converter. The purpose of using a PFC Rectifier as the front-end is to achieve a close to unity power factor and low harmonics content. The circuit is designed from data obtained from a conventional AC/DC/AC converter. The results from the experiments show that, using the PFC rectifier, the power factor is close to unity and the %THD (Total Harmonic Distortion Percentage) is smaller than the obtained using a diode bridge front-end.